Indices of agricultural production in Western Europe, 1950-68 - United States. Department of Agriculture, Economic Research Service (Washington, D.C. : 1969, 1969)
Western Europe contains about 335 million people. With income and living standards among the world's highest, the population of the region consumes a large share of the world's food and fiber. A large portion of the world's supply of temperate commodities is produced in the region but a very high man land ratio makes the region a large net importer of food and fiber. Assessment of the agricultural and food situation in this area of the world and its development over time is critical to a knowledge of the world situation. The indices presented in this publication are a part of the continuing effort of the Economic Research Service to assess the world agricultural situation. This is the first time that detailed indices for this part of the world have been published by the U.S. Department of Agriculture, although indices of aggregate output have been published for several years.
Cover title.
lje 06/07/2017
Loans
Keywords: Agriculture--Economic aspects